Assessment on the Role of the Nigerian Media in Educating the Children and Adolescent on the Value of Sex Education - Joshua Kayode Okunade; Timothy Ekeledirichukwu Onyejelem; Esther Ukpe; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
This study focused on the assessment of the role of the Nigerian media in educating the children and adolescent on the value of sex education, using two educational institutions in Lagos State. The research study adopted the survey method to collect data for an in-depth analysis, the researchers conducted a descriptive study with four objectives and four research questions. A total of 300 adolescents were randomly selected from among the 60865 students enrolled in Cedec International Secondary School and undergraduates of the University of Lagos State (Unilag) as part of a purposive sampling strategy for the research study. Data was gathered through the use of a questionnaire, which was then analyzed and summarized using frequency and percentage. The findings of this research show that most of the adolescents have insufficient knowledge about sex education therefore adolescents require scientific, religious and factual information to help them develop positive sexual attitudes and responsible healthy behaviors Moreover, most of the respondents agreed to the fact that sex education is effective, but most of them do not have sufficient knowledge so they require knowledge to prevent them from inventing their own mythologies and developing anti-social behaviors. Thus, the study recommends the encouragement of more sex education contents or programme in the Nigerian media through creditable sources such as national televisions and radios.